Response surface method-based RAP-steel slag regenerated asphalt mixture optimal ratio and Gr-TiO2 doping method
By optimizing the mixing ratio of RAP and steel slag and introducing Gr-TiO2 doping through response surface methodology, the problems of low mixing efficiency and unbalanced performance of RAP and steel slag recycled asphalt mixture were solved, and efficient and accurate preparation and performance improvement of recycled asphalt mixture were achieved.
Patent Information
- Application Number
- CN202511204310.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-27
- Publication Date
- 2025-10-03
AI Technical Summary
The existing technology is inefficient in determining the mixing ratio of RAP and steel slag, consumes a lot of materials, and is difficult to achieve a balanced road performance of the recycled asphalt mixture, resulting in low solid waste utilization efficiency.
The response surface methodology was used to design the optimal mix ratio of RAP-steel slag recycled asphalt mixture, and Gr-TiO2 doping was introduced. Through multi-factor interaction modeling, the material proportion and performance were optimized, and Gr-TiO2 was used to improve the interfacial bonding and asphalt film continuity.
Significantly reduce the number of tests and resource consumption, achieve efficient and accurate proportioning of recycled asphalt mixture, improve road performance, and promote high-value utilization of solid waste.
Smart Images

Figure CN120748541A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of road asphalt mixture preparation, and in particular to an optimal ratio of RAP-steel slag recycled asphalt mixture and a Gr-TiO2 doping method based on response surface methodology. Background Art
[0002] With the rapid development of my country's transportation infrastructure, older roads are entering a peak period of maintenance, resulting in a significant amount of recycled asphalt mixture (RAP). Simultaneously, the continued growth of the steel industry has led to increasing emissions of steel slag. The large-scale storage of these two industrial solid wastes not only occupies land and wastes resources, but also poses environmental risks. Therefore, the synergistic use of RAP and steel slag in road construction to replace natural aggregates in the production of recycled asphalt mixtures has become an important approach to reclaiming solid waste, conserving natural resources, and achieving both economic and environmental benefits.
[0003] However, existing technologies mostly use empirical or single-variable test methods to determine the mixing ratio of RAP or steel slag. For example, Qin Yu (Mix ratio design and performance verification of recycled asphalt mixture with steel slag [J]. Inner Mongolia Highway and Transportation, 2024, (6): 43-47.) used empirical proportioning to verify that steel slag can replace natural aggregate and be compounded with RAP to produce recycled asphalt mixture with steel slag, so that it meets the performance requirements of the pavement layer. Liu Xiaoxu (Effect of steel slag content on the road performance of recycled asphalt mixture [J]. Transportation World, 2025, (10).) also used AC-13 dense graded asphalt mixture as the benchmark gradation and used empirical proportioning to study the pavement performance after adding RAP and steel slag, especially the anti-skid performance. It is necessary to consider the risk of excessive reduction in anti-skid ability due to increased RAP content, and at the same time improve the mixing ratio of RAP and steel slag.
[0004] Such methods typically require extensive trial-and-error testing, resulting in cumbersome processes and significant material consumption. This is not only inefficient but also prone to producing excessive experimental waste, undermining the original intention of environmental protection. More importantly, when two solid waste materials with distinct properties, RAP and steel slag, are introduced simultaneously, simple empirical proportioning makes it difficult to precisely control their interaction and compatibility with asphalt. This often results in the recycled asphalt mixture's road performance (such as high-temperature stability, water stability, and low-temperature crack resistance) struggling to achieve optimal balance, and can even lead to performance shortcomings, limiting the high-value, large-scale utilization of solid waste.
[0005] Therefore, there is an urgent need for a scientific and systematic method that can break through the limitations of traditional empirical design to efficiently and accurately optimize the amount of RAP and steel slag in recycled asphalt mixtures. Summary of the Invention
[0006] In view of this, the present invention proposes an optimal ratio of RAP-steel slag recycled asphalt mixture and Gr-TiO2 (graphene-doped titanium dioxide) doping method based on response surface methodology. It comprehensively considers the interaction between multiple factors, significantly reduces the number of tests and resource consumption, and achieves comprehensive prediction and optimization of key road performance indicators of the mixture while avoiding the generation of a large amount of test waste.
[0007] The technical solution of the present invention is achieved as follows: In a first aspect, the present invention provides a method for designing an optimal mix ratio of RAP-steel slag recycled asphalt mixture based on a response surface methodology, comprising the following steps: Step 1: Design the base gradation of basalt aggregate according to AC-16 dense gradation, including 0-3mm basalt fine aggregate, 3-5mm basalt transitional aggregate, 5-10mm basalt coarse aggregate and 10-20mm basalt coarse aggregate; Step 2: Gradually replace the 5-10 mm basalt coarse aggregate and the 10-20 mm basalt coarse aggregate in the reference gradation with RAP and steel slag according to a preset volume ratio; Step 3: Using the volume proportion of 5-10mm RAP, the volume proportion of 10-20mm RAP, and the oil-stone ratio as three factors, a three-factor, three-level BBD design was used to generate multiple experimental plans; Step 4: preparing multiple groups of recycled asphalt mixture specimens according to the multiple test schemes, and obtaining the Marshall stability, flow value, bulk density, mineral gap ratio, void ratio and asphalt saturation of the recycled asphalt mixture specimens as response values; Step 5: constructing a response surface regression model based on the response value; Step 6: Solve the response surface regression model to obtain the optimal gradient volume replacement ratio and the optimal oil ratio of the RAP-steel slag recycled asphalt mixture.
[0008] Furthermore, in step 2, the volume replacement ratio gradient of the RAP is set to 0%, 25%, and 50%; the volume replacement ratio gradient of the slag is set to 100%, 75%, and 50%.
[0009] Furthermore, in step three, the three factors and three levels are: Factor A: 5-10mm RAP volume proportion, levels are 0%, 25%, and 50%; Factor B: 10-20mm RAP volume proportion, levels are 0%, 25%, and 50%; Factor C: oil-stone ratio, levels are 4.0%, 4.5%, and 5.0%.
[0010] Furthermore, in step 4, the asphalt in the recycled asphalt mixture specimen is 90# road petroleum asphalt, and the filler is basalt mineral powder; the preparation temperature of the recycled asphalt mixture specimen is 170-190°C.
[0011] Furthermore, the design method also includes: Step 7, based on the optimal gradient volume replacement ratio and optimal oil ratio of the RAP-steel slag recycled asphalt mixture, Gr-TiO2 is used to replace basalt mineral powder to prepare the recycled asphalt mixture.
[0012] Furthermore, the Gr-TiO2 replacement ratio is 0% to 75% of the total volume of the basalt slag powder.
[0013] Furthermore, the Gr-TiO2 replacement ratio is 25% to 50% of the total volume of the basalt slag powder.
[0014] Furthermore, in step 5, the response surface regression model is constructed using a second-order polynomial regression equation, which is expressed as follows:
[0015] Where: Indicates the response value, is a constant term, , There are three factors and three levels. is the coefficient of the first-order term, is the coefficient of the quadratic term, is the interaction term coefficient.
[0016] In a second aspect, the present invention relates to a recycled asphalt mixture designed and prepared using the above-mentioned RAP-steel slag recycled asphalt mixture optimal ratio design method based on response surface methodology.
[0017] In a third aspect, the present invention relates to the application of the above-mentioned recycled asphalt mixture in road engineering.
[0018] The optimal ratio of RAP-steel slag recycled asphalt mixture and Gr-TiO2 doping method based on response surface methodology of the present invention have the following beneficial effects compared with the prior art: (1) The present invention adopts the response surface methodology and, through comprehensive optimization of multiple indicators, accurately determines the optimal gradient replacement ratio and the optimal oil-stone ratio of RAP and steel slag at different particle size levels, thus solving the problems of repeated experiments, material waste, and unbalanced road performance caused by traditional empirical design.
[0019] (2) The recycled asphalt mixture provided by the present invention is rationally doped with a certain amount of Gr-TiO2 on the basis of the determined optimal ratio of the two solid wastes, thereby realizing the scientific application of functional materials and further improving the comprehensive road performance of the mixture.
[0020] (3) The present invention provides a simple, efficient and scientific path for the synergistic high-value utilization of RAP-steel slag dual solid waste. It not only significantly improves the utilization rate of waste materials in actual engineering, but also ensures the improvement of the overall utilization efficiency of recycled asphalt mixture through multi-factor and multi-objective optimization, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0022] Figure 1 This is a three-dimensional response surface diagram obtained based on the response surface regression model in Example 1 of the present invention; Figure 2 This is a two-dimensional contour map obtained based on the response surface regression model in Example 1 of the present invention. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0024] To accurately determine the optimal mix ratio for recycled asphalt mixtures using RAP and steel slag as dual solid wastes, while also further improving the overall performance of the recycled asphalt mixture, the inventors proposed a scientific design and optimization method based on the response surface methodology. This method first uses a systematic experimental design to comprehensively consider the interactive effects of multiple factors, including RAP dosage, steel slag dosage, and oil-to-stone ratio, to establish a mathematical model to determine the optimal mix ratio under the synergistic effects of the two solid wastes.
[0025] In addition, the inventors took into account the possible problems of the dual solid waste materials themselves, and aimed at the problems that the aged asphalt components in RAP are prone to migration, resulting in a decrease in interfacial adhesion, and the porous structure of steel slag adsorbing asphalt and reducing the effective film thickness. Based on the optimal ratio, the present invention further introduced Gr-TiO2 as a functional filler.
[0026] Gr-TiO2, with its high specific surface area, can fill RAP microcracks and cover steel slag pores, improving interfacial defects and enhancing asphalt film continuity. Its photocatalytic effect can decompose asphalt aging products, while graphene doping helps enhance its activity, promoting the generation of free radicals to degrade polar components. Graphene and asphalt can form hydrogen bonds or ester bonds, while TiO2 and asphalt can form Ti-OC bonds, synergistically strengthening interfacial chemical bonding. Furthermore, during road use, TiO2 absorbs ultraviolet light to delay secondary aging, while graphene helps rearrange asphalt molecules and promotes self-healing of microcracks, thereby comprehensively improving the road performance of the dual-solid waste recycled asphalt mixture.
[0027] Therefore, the inventors adopted the method of replacing basalt mineral powder with an equal volume of Gr-TiO2, and by exploring the influence of its dosage on key road performance of the mixture such as high-temperature stability, water stability and low-temperature crack resistance, they defined the reasonable doping range of Gr-TiO2, and ultimately achieved the dual goals of efficient utilization of solid waste and synergistic improvement of material performance.
[0028] The regenerated asphalt mixture provided by the present invention comprises: 0-3mm basalt fine aggregate, 3-5mm basalt transition aggregate; 5-10mm grade basalt coarse aggregate: Set a gradient replacement ratio, including three groups, with RAP accounting for 0%, 25%, and 50% of the aggregate volume in this grade, and steel slag as a complementary material to RAP, which is replaced simultaneously at 100%, 75%, and 50% of the volume in this grade; the sum of the volume proportions of RAP and steel slag in this grade of aggregate is always 100%; 10-20mm grade basalt coarse aggregate: Set a gradient replacement ratio, including three groups, with RAP accounting for 0%, 25%, and 50% of the aggregate volume in this grade, and steel slag as a complementary material to RAP, which is replaced simultaneously at 100%, 75%, and 50% of the volume in this grade; the sum of the volume proportions of RAP and steel slag in this grade of aggregate is always 100%; The filler includes basalt mineral powder and / or Gr-TiO2 powder; the binder is No. 90 road petroleum asphalt.
[0029] The present invention will be further described below with reference to specific examples. Unless otherwise specified, the materials mainly involved in the examples are commercially available conventional products.
[0030] Example 1 This embodiment provides a method for designing the optimal ratio of RAP-steel slag recycled asphalt mixture based on response surface methodology, which specifically includes the following steps: Step 1: Design the base gradation of basalt aggregate (purchased from Jinshun Sand and Stone Co., Ltd., Hohhot, Inner Mongolia) according to AC-16 dense gradation, including 0-3mm basalt fine aggregate, 3-5mm basalt transitional aggregate, 5-10mm basalt coarse aggregate and 10-20mm basalt coarse aggregate; Step 2: synchronously gradient-replace the 5-10 mm basalt coarse aggregate and the 10-20 mm basalt coarse aggregate in the benchmark gradation. The specific replacement scheme is as follows: the volume proportion of RAP is set to 0%, 25%, and 50%. Correspondingly, the volume proportion of steel slag as a complementary material is simultaneously set to 100%, 75%, and 50%. The 0-3 mm and 3-5 mm aggregates remain 100% basalt. Step 3. Using the 5-10mm RAP volume proportion, 10-20mm RAP volume proportion, and oil-stone ratio as the three factors, a three-factor, three-level design was performed using BBD, including: Factor A: 5-10mm RAP volume proportion, with levels of 0%, 25%, and 50%; Factor B: 10-20mm RAP volume proportion, with levels of 0%, 25%, and 50%; Factor C: oil-stone ratio, with levels of 4.0%, 4.5%, and 5.0%. Using the BBD three-factor, three-level response surface design method, 15 experimental schemes were generated, including three groups of center points (factors A, B, and C all took the middle levels of 25%, 25%, and 4.5%) for repeated verification of the stability of the experiment. Step 4: In accordance with the relevant provisions of the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011), use 90# road petroleum asphalt and mix it in an automatic asphalt mixture mixer at a mixing temperature of 180°C. Mix the various aggregates, basalt powder (purchased from Qirui Basalt Technology Co., Ltd., Hohhot, Inner Mongolia) and 90# road petroleum asphalt (purchased from Luxin Asphalt Concrete Co., Ltd., Hohhot, Inner Mongolia) and conduct the following tests: (1) The mixed material was compacted on a Marshall compactor according to the standard method (75 times on each side) to form standard Marshall specimens (diameter 101.6 mm, height 63.5 mm). Four parallel specimens were prepared for each test. The formed specimens were kept in a constant temperature water bath at 60°C ± 1°C for 35 minutes before the Marshall test. The loading was carried out at a loading rate of 50 mm / min, and the maximum load (stability, unit: kN) and the corresponding deformation (flow value, unit: 0.1 mm) at the time of specimen failure were recorded. (2) The bulk density of the specimen is measured by the surface dry method (unit: g / cm³) and calculated according to the following formula:
[0031] Where, is the gross volume density, To measure the air mass of the dry specimen, is the surface dry mass, The mass in water.
[0032] (3) The theoretical maximum relative density is calculated according to the method of test procedure T 0711-1, thereby obtaining the void ratio, mineral gap ratio and asphalt saturation of the recycled asphalt mixture: Theoretical maximum relative density: ; In the formula, in the formula, is the theoretical maximum relative density, m a is the mass of the dry asphalt mixture sample in air, m1 is the mass of the negative pressure container in 25℃ water, and m2 is the mass of the negative pressure container and asphalt mixture in 25℃ water; Void ratio: ; Where, is the void ratio, is the relative density of gross volume, The theoretical maximum relative density Mineral void ratio: ; Where, is the void ratio of the ore, is the mass percentage of the ore, is the relative density of the synthetic gross volume of the mineral aggregate; Asphalt saturation: ; Where, is the asphalt saturation, is the void ratio of the ore, is the void ratio.
[0033] Marshall stability, flow value, bulk density, aggregate interstitial ratio, void ratio and asphalt saturation were used as response values of the response surface methodology. The specific parameters and response value results of the 15 groups of experiments are shown in Table 1. Table 1 Test data of 15 experimental schemes
[0034] Step 5: Based on the 15 sets of experimental data obtained in step 4 (factors A, B, C and their corresponding 6 response values), a response surface regression model was constructed using statistical analysis software and a second-order polynomial regression equation, as shown below:
[0035] Where: Indicates the response value, is a constant term, , There are three factors and three levels. is the coefficient of the first-order term, is the coefficient of the quadratic term, is the interaction term coefficient.
[0036] Step 6: Use the established response surface regression model to draw a three-dimensional response surface diagram (such as Figure 1 ) and two-dimensional contour maps (as shown in Figure 2 ), and intuitively analyze the impact trend of each factor and its interaction on the response value.
[0037] Combine Figure 1 、 2 It can be seen that the present invention finally determines the optimal ratio of RAP-steel slag recycled asphalt mixture as follows: the volume proportion of 5-10mm grade RAP is 25.95%, and the volume proportion of 10-20mm grade RAP is 25.95%. Correspondingly, the volume proportions of the two grades of steel slag are both 74.05%, and the optimal oil-stone ratio is 4.56%.
[0038] Example 2 Based on Example 1, this example provides a solution for replacing basalt powder with an equal volume of Gr-TiO2 powder (purchased from Hangzhou Zheming New Materials Co., Ltd.), comprising the following steps: Step 7. Based on the optimal gradient volume replacement ratio and optimal oil ratio of RAP-steel slag recycled asphalt mixture determined in Example 1, Gr-TiO2 is used to replace basalt mineral powder to prepare recycled asphalt mixture, with replacement ratios of 0%, 25%, 50%, and 75%. In this way, four groups of Gr-TiO2-doped dual-solid waste recycled asphalt mixture specimens were prepared, and were marked as Group A (0% Gr-TiO2), Group B (25% Gr-TiO2), Group C (50% Gr-TiO2), and Group D (75% Gr-TiO2).
[0039] The road performance tests of the above four groups of test pieces include: (1) High temperature stability: Dynamic stability (DS, unit: times / mm) is measured by rutting test, which is used to evaluate the ability of recycled asphalt mixture to resist permanent deformation under repeated vehicle rolling; (2) Water stability: The residual stability (MS) was determined by the water immersion Marshall test. o ,%), and the residual strength ratio (TSR,%) was measured by freeze-thaw splitting test to evaluate the ability of the mixture to resist water damage; (3) Low-temperature crack resistance: The maximum bending strain (εb, unit: με) is measured through the low-temperature bending test to evaluate the ability of the mixture to withstand tensile deformation at low temperatures; (4) Anti-skid performance: At 20°C, the pavement pendulum value is tested using a pendulum friction coefficient tester, and the structural depth (TD, unit: mm) is tested using the volume method or laser scanning method to evaluate the pavement's anti-skid and drainage capabilities.
[0040] The test results are shown in Table 2 and Table 3.
[0041] Table 2 Road performance indicators
[0042] Table 3 Anti-slip performance index
[0043] As shown in Table 2, compared with group A, the dynamic stability of groups B, C, and D is significantly improved, that is, the addition of Gr-TiO2 powder can effectively improve the ability to resist high-temperature rutting, and the four groups of RAP-steel slag reach a dosage balance through the optimal ratio of the response surface method, and the high-temperature stability of RAP is excellent. The residual stability, residual strength ratio, and maximum bending strain of groups A, B, and C all meet the requirements of the specifications, that is, the water stability and low-temperature crack resistance are excellent. However, the addition of 75% Gr-TiO2 in group D will cause the water stability and low-temperature crack resistance to drop to levels outside the specification requirements. This may be due to the agglomeration of highly doped Gr-TiO2 powder, which makes it unevenly dispersed in the asphalt, resulting in a significant decrease in the performance of the dual-solid waste recycled asphalt mixture, which does not meet its use requirements. Therefore, the inventor further suggests that controlling the addition of Gr-TiO2 between 25 and 50% can achieve the optimal road performance of the recycled asphalt mixture.
[0044] As can be seen from Table 3, the pendulum value and structural depth of group D are only 53 and 0.3702 mm, respectively. Its structural depth cannot meet the technical requirement of not less than 0.55 in the "Field Test Code for Highway Roadbed and Pavement" (JTG 3450-2019). This indicates that the doping of 75% Gr-TiO2 breaks the balance of the optimal ratio of RAP-steel slag, and the Gr-TiO2 powder agglomerates over a large area in the asphalt mixture and adheres to the pores on the surface of the steel slag, resulting in a decrease in anti-skid and wear resistance. Compared with group A, groups B and C are within a reasonable range of Gr-TiO2 doping ratios, and as the doping ratio of Gr-TiO2 increases, the pendulum value and structural depth increase accordingly, and are both within the range of specification requirements. This is because a reasonable proportion of Gr-TiO2 will be evenly dispersed in the asphalt, thereby filling the tiny pores in the asphalt mixture, thereby improving the anti-skid performance of the dual-solid waste recycled asphalt mixture.
[0045] In summary, when Gr-TiO2 is doped at the optimal ratio of the recycled asphalt mixture prepared by the present invention and its dosage range is controlled between 25% and 50%, it can be used as a recycled pavement material to effectively improve the pavement performance. This is mainly due to the rigid skeleton effect of the nanoparticles: the two-dimensional layer structure of graphene is interspersed in the asphalt mortar, and cooperates with titanium dioxide to construct a three-dimensional network structure, which significantly inhibits the deformation of RAP at high temperatures.
[0046] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for designing the optimal mix ratio of RAP-steel slag recycled asphalt mixture based on response surface methodology, characterized in that: The following steps are involved: Step 1: Design the base gradation of basalt aggregate according to AC-16 dense gradation, including 0-3mm basalt fine aggregate, 3-5mm basalt transitional aggregate, 5-10mm basalt coarse aggregate and 10-20mm basalt coarse aggregate; Step 2: Gradually replace the 5-10 mm basalt coarse aggregate and the 10-20 mm basalt coarse aggregate in the reference gradation with RAP and steel slag according to a preset volume ratio; Step 3: Using the volume proportion of 5-10mm RAP, the volume proportion of 10-20mm RAP, and the oil-stone ratio as three factors, a three-level BBD design was used to generate multiple experimental plans; Step 4: preparing multiple groups of recycled asphalt mixture specimens according to the multiple test schemes, and obtaining the Marshall stability, flow value, bulk density, mineral gap ratio, void ratio and asphalt saturation of the recycled asphalt mixture specimens as response values; Step 5: constructing a response surface regression model based on the response value; Step 6: Solve the response surface regression model to obtain the optimal gradient volume replacement ratio and the optimal oil ratio of the RAP-steel slag recycled asphalt mixture.
2. The optimal mix design method of RAP-steel slag recycled asphalt mixture based on response surface methodology according to claim 1, characterized in that: In step 2, the volume replacement ratio gradient of the RAP is set to 0%, 25%, and 50%; the volume replacement ratio gradient of the slag is set to 100%, 75%, and 50%.
3. The optimal mix design method of RAP-steel slag recycled asphalt mixture based on response surface methodology according to claim 1, characterized in that: In step 3, the three factors and three levels are: Factor A: RAP volume proportion in the 5-10mm range, with levels of 0%, 25%, and 50%; Factor B: RAP volume proportion in the 10-20mm range, with levels of 0%, 25%, and 50%; Factor C: asphalt-stone ratio, with levels of 4.0%, 4.5%, and 5.0%.
4. The optimal mix design method of RAP-steel slag recycled asphalt mixture based on response surface methodology according to claim 1, characterized in that: In step 4, the asphalt in the recycled asphalt mixture specimen is 90# road petroleum asphalt, and the filler is basalt mineral powder; the preparation temperature of the recycled asphalt mixture specimen is 170-190°C.
5. The optimal mix design method of RAP-steel slag recycled asphalt mixture based on response surface methodology according to claim 4, characterized in that: The design method further includes: Step 7: Based on the optimal gradient volume replacement ratio and the optimal oil ratio of the RAP-steel slag recycled asphalt mixture, Gr-TiO2 is used to replace the basalt mineral powder to prepare the recycled asphalt mixture.
6. The optimal mix design method of RAP-steel slag recycled asphalt mixture based on response surface methodology according to claim 5, characterized in that: The Gr-TiO2 replacement ratio is 0% to 75% of the total volume of the basalt slag powder.
7. The optimal mix design method of RAP-steel slag recycled asphalt mixture based on response surface methodology according to claim 5, characterized in that: The Gr-TiO2 replacement ratio is 25% to 50% of the total volume of the basalt slag powder.
8. The optimal mix design method of RAP-steel slag recycled asphalt mixture based on response surface methodology according to claim 1, characterized in that: In step 5, the response surface regression model is constructed using a second-order polynomial regression equation, which is expressed as: ; Where: Indicates the response value, is a constant term, , There are three factors and three levels. is the coefficient of the first-order term, is the coefficient of the quadratic term, is the interaction term coefficient.
9. A recycled asphalt mixture, characterized in that: The regenerated asphalt mixture is designed and prepared by using the optimal mix design method of RAP-steel slag regenerated asphalt mixture based on response surface methodology as described in any one of claims 1 to 8.
10. Use of the recycled asphalt mixture according to claim 9 in road engineering.
Citation Information
Patent Citations
Mix proportion design method of plant-mixed hot recycled asphalt mixture
CN111548057A
Thermal regeneration steel slag asphalt mixture and preparation method thereof
CN113511842A
Method and device for determining optimal mix proportion of asphalt mixture based on response surface method
CN117497107A
Mix proportion design method of recycled asphalt concrete doped with steel slag
CN117877637A
Asphalt concrete mixture containing steel slag and recycled aggregate
KR102341684B1